BrdU replication patterns demonstrating chromosome homoeologies in two fish species, genus Eigenmannia - Almeida Toledo, L. F.; Viegas-Péquignot, E.; Foresti, F. [UNESP]; Toledo Filho, S. A.; Dutrillaux, Bernard [UNESP] (Karger Publishers, 1988)
The karyotypes of two fish species (genus Eigenmannia) from Brazilian rivers were studied with various chromosome banding techniques. BrdU incorporation appears to be the most powerful method for identifying chromosome homoeologies between karyotypes. It also demonstrates asymmetrical hcterochro-matic segments, suggesting an uneven distribution of A-T base pairs in the two DNA strands. In one of these species, males differ from females by the acquisition of a Robertsonian translocation, resulting in a loss of a heterochromatic segment, which may be related to sex differentiation. © 1988 S. Karger AG. Basel.